WAGE (UJRAH) IN THE CONCEPT OF IJARAH BI AL-AMAL: A PERSPECTIVE OF SHAFI'I SCHOLARS - Paizun Paizun; Dallah; Said Muhammad Rahimin (SOSIOEDUKASI, 2026)
This study aims to examine the normative construction of ujrah (wage) within ijarah bi al-amal according to Shafi'i jurisprudence and to analyze the extent to which contemporary labor-based service transactions align with or depart from its doctrinal standards. Employing a qualitative library research approach with descriptive-analytical method, this study draws upon classical Shafi'i juristic texts and peer-reviewed contemporary scholarship as its primary data sources, analyzed through content analysis and comparative juristic method with source triangulation to ensure validity. The findings reveal two principal conclusions. First, Shafi'i jurisprudence constructs ujrah as a dynamic protective normative system, not merely a set of formal validity conditions, grounded in contractual clarity (ma'lum), prohibition of uncertainty (gharar), and the principle of istihqaq al-ujrah bi al-'amal, with ujrah al-mithl serving as a built-in corrective mechanism against wage deprivation. Second, contemporary ujrah applications demonstrate partial doctrinal alignment, mediated through the adaptive invocation of 'urf jari and cultural internalization of Shafi'i norms, enabling transactional success even without formal institutional oversight. These findings contribute new theoretical insights to Islamic labor contract scholarship and carry direct implications for advancing SDG 8 on Decent Work and SDG 1 on poverty reduction within Muslim-majority labor markets.